The Unwound Cochlea: A Specific Imaging Marker of Branchio-Oto-Renal Syndrome - Hsu, A.; Desai, N.; Paldino, M.J. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Branchio-oto-renal syndrome is an important syndromic cause of hearing loss. Our aim was to determine the test characteristics of the unwound cochlea on temporal bone CT for the diagnosis of branchio-oto-renal syndrome in a cohort of children with hearing loss.MATERIALS AND METHODS: Patients were identified retrospectively with a clinical diagnosis of branchio-oto-renal syndrome and CT imaging of the temporal bones. Age-matched controls were also identified with sensorineural hearing loss not related to a diagnosis of branchio-oto-renal syndrome and CT imaging of the temporal bones. All examinations were reviewed by 2 neuroradiologists blinded to the diagnosis of branchio-oto-renal syndrome versus controls for the absence/presence of an unwound cochlea defined as anteromedial rotation and displacement of the middle and apical turns away from the basal turn.RESULTS: The final study group comprised 9 patients with branchio-oto-renal syndrome (age range, 1–14 years; mean age, 8.0 ± 4.3 years) and 50 control patients (age range, 1–16 years; mean age, 7.9 ± 4.1 years). The cochlea was subjectively abnormal in all 9 patients. In 8 patients (89%), imaging demonstrated a typical unwound cochlear morphology. By contrast, none of the control subjects demonstrated an unwound cochlea on either side. Statistically, the unwound cochlea was significantly more frequent in the branchio-oto-renal group compared with controls (P < .001). The unwound cochlea was 89% sensitive and 100% specific for the diagnosis of branchio-oto-renal syndrome.CONCLUSIONS: The unwound cochlea is a specific imaging marker of branchio-oto-renal syndrome. These findings further support the diagnostic accuracy and therefore the utility of temporal bone imaging in the diagnosis of this disorder.BORbranchio-oto-renal syndrome